Isolation and characterisation of the Drosphila dror2 gene : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Genetics at Massey University, Palmerston North, New Zealand - Frith, Kathryn Joy (Massey University, 1997)
Receptor tyrosine kinases (RTKs) are a family of cell-surface receptors that have an important role in an array of cellular responses including cell migration, proliferation and differentiation (Fantl et al., 1993). RTKs and their ligands are important components in the determination of cell fate through signalling pathways that are activated during both invertebrate and vertebrate development (Pawson and Bernstein, 1990). The Ror subfamily of RTKs are thought to be important for the development of the nervous system as they are expressed highly in the nervous system in the developing embryo, but expression is minimal in adults. Three receptors in this subfamily have been identified. Rorl and Ror2 from humans (Masiakowski and Carroll, 1992) and Dror from Drosophila (Wilson et al., 1993). This thesis involved the isolation and characterisation of the fourth gene in this family Dror2 from Drosophila melanogaster. Degenerate oligonucleotides to conserved regions of the tyrosine kinase domain of RTKs were used to PCR amplify a 200 bp fragment from genomic DNA. A λ genomic library was screened with the labelled fragment in order to isolate the gene. The resulting clone was subcloned and sequenced to obtain the complete sequence of Dror2. The 3' end of the gene was determined by RT-PCR. The transcriptional start point was identified by using 5' RACE and sequencing of the amplification product. Expression of Dror2 was examined using Northern Blot hybridisation and in situ hybridisation to whole mount embryos. The 725 amino acid mature Dror2 protein comprises an extracellular domain containing the signal peptide, cysteine-rich region and kringle domain, a hydrophobic transmembrane domain and the intracellular domain containing a catalytic kinase domain. Three introns were identified, one in the middle of the cysteine-rich region and two flanking the kringle domain.
Keywords: Drosophila melanogaster; Genetics